2015
DOI: 10.1016/j.psi.2015.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Psychological injury in victims of child sexual abuse: A meta-analytic review

Abstract: In order to assess the effects of child/adolescent sexual abuse (CSA/ASA) on the victim's probability of developing symptoms of depression and anxiety, to quantify injury in populational terms, to establish the probability of injury, and to determine the different effects of moderators on the severity of injury, a meta-analysis was performed. Given the abundant literature, only studies indexed in the scientific database of reference, the Web of Science, were selected. A total of 78 studies met the inclusion cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(76 citation statements)
references
References 89 publications
(27 reference statements)
3
67
0
6
Order By: Relevance
“…Steet children informants admitted that if they did not implement the behavior in coping biopsychosocial impacts generated by sexual violence, then sexual violence they experienced would turninto a particular trauma for them and the emotion they felt would be getting bigger if they happened to come across the perpetrators. It is in line with what stated by Amado et al, (2015) that sexual violence criminal act may give serioud impact to the victims such as mental injuries and emotional suffering, major depression disorder, persistent depressive disorder, phobia and anxiety.…”
Section: E Perceived Barriersupporting
confidence: 89%
“…Steet children informants admitted that if they did not implement the behavior in coping biopsychosocial impacts generated by sexual violence, then sexual violence they experienced would turninto a particular trauma for them and the emotion they felt would be getting bigger if they happened to come across the perpetrators. It is in line with what stated by Amado et al, (2015) that sexual violence criminal act may give serioud impact to the victims such as mental injuries and emotional suffering, major depression disorder, persistent depressive disorder, phobia and anxiety.…”
Section: E Perceived Barriersupporting
confidence: 89%
“…To the best of our knowledge, no previous meta‐analysis has examined the direct relationship between CSA and depression with a special focus on the age at onset, although an abundance of previous reviews has examined the link between CSA and depression in terms of exposure, occurrence or severity (e.g. Amado et al, ; Lindert et al, ; Neumann et al, ). Some of these articles (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent reviews by Carr, Duff, and Craddock (, ) similarly found that CSA survivors were at a higher risk of a range of psychosocial, physical and mental health difficulties. Systemic reviews have also specifically established that CSA is a risk factor for depression, anxiety, Post Traumatic Stress Disorder (PTSD) (Amado, Arce, & Herraiz, ; Hillberg, Hamilton‐Giachritsis, & Dixon, ); sexual exploitation (De Vries & Goggin, ), intimate partner violence (Li, Zhao, & Yu, ), suicidality (Angelakis, Gillespie & Panagioti, ), substance abuse (Halpern et al, ), and educational difficulties (Fry et al, ). Reviews have also demonstrated a range of psychosocial protective factors that can help reduce risk, including family and social supports, personal attributes, active coping style, a sense of personal influence, and externalising blame for the abuse (Carr, Duff, & Craddock, , ).…”
Section: Introductionmentioning
confidence: 99%